Enhancement of Iron Acquisition in Rice by the Mugineic Acid Synthase Gene With Ferric Iron Reductase Gene and OsIRO2 Confers Tolerance in Submerged and Nonsubmerged Calcareous Soils - Masuda, Hiroshi; Aung, May Sann; Kobayashi, Takanori; Hamada, Tatsuro; Nishizawa, Naoko K. (Frontiers in Plant Science, 2019)
Iron (Fe) deficiency is a critical agricultural problem, especially in calcareous soil, which covers more than 30% of the Earth’s surface. Rice plants take up Fe(II) from soil through an OsIRT1 transporter (Strategy I-related system) and Fe(III) via a phytosiderophore-based system (Strategy II system). However, they are susceptible to low-Fe availability such as in calcareous soil with high pH because they have low Fe(III) reduction activity and low-level phytosiderophore secretion. Previously, we produced transgenic rice plants expressing a mutationally reconstructed yeast ferric reductase, refre1/372, under the control of the OsIRT1 promoter. These plants exhibited higher Fe(III) chelate-reductase activity and tolerance to Fe deficiency. In addition, we produced transgenic rice overexpressing the Fe deficiency-inducible transcription factor, OsIRO2, which regulates the expression of various genes involved in the Strategy II Fe(III) uptake system, including OsNAS1, OsNAAT1, OsDMAS1, OsYSL15, and TOM1. Those plants exhibited improved phytosiderophore secretion ability and tolerance to low Fe availability. Moreover, introduction of a barley mugineic acid synthase gene, IDS3, which enhanced phytosiderophore productivity, resulted in low Fe availability tolerance during calcareous soil cultivation. In the present study, transgenic rice plants with an barley IDS3 genome fragment, OsIRT1 promoter-refre1/372, and a 35S promoter-OsIRO2 (IRI lines) were produced to enhance both Strategy I Fe(II) reductase ability and Strategy II phytosiderophore productivity. Our results show that in calcareous soil cultivation under submerged conditions, IRI lines exhibited a 9-fold higher yield than the non-transgenic line. In addition, IRI lines exhibited enhanced tolerance to Fe-deficient conditions compared to the non-transgenic line and lines harboring the 35S promoter-OsIRO2 or the IDS3 fragment. Moreover, IRI lines also exhibited enhanced tolerance than the non-transgenic line, lines harboring only the OsIRT1 promoter refre1/372 or OsIRO2, and lines harboring both under non-submerged calcareous conditions. Our results demonstrate that further enhancement of the Strategy II Fe uptake system by the mugineic acid synthase gene in addition to Fe uptake by enhanced ferric Fe reduction and phytosiderophore production in rice is highly effective for conferring tolerance to low Fe availability in calcareous soil under paddy or non-paddy field conditions.